Influencing factors of adherence to sustainable diets: a systematic review of behavioral theories - Seyedeh Fatemeh Fatemi; Seyedeh Fatemeh Fatemi; Hadi Tehrani; Hadi Tehrani; Maryam Khosravi; Maryam Khosravi; Hassan Doosti; Niloufar Rasaei; Seyyed Reza Sobhani (Frontiers in Sustainable Food Systems)
This systematic review aims to identify factors influencing adherence to a sustainable diet based on behavioral theories. We searched four databases, including PubMed, Web of Science, Scopus, and Science Direct, for observational studies assessing sustainable food consumption according to the Theory of Planned Behavior (TPB), the Theory of Reasoned Action (TRA), and the Social Cognitive Theory (SCT) up to December 01, 2023. Additionally, the reference lists of original studies were screened, and 12 papers were analyzed. In identifying triggers for consumers’ behavioral changes, we found that improving food choice skills is a valuable strategy to enhance an individual’s perceived control and ability to adopt sustainable eating behaviors. The most recurrent predictors for sustainable food choices were attitudes, Perceived Behavioral Control, subjective norms, experience, and personal factors. This study provides valuable insights into the factors influencing consumer behavior and offers opportunities to promote sustainable food choices.